Efficacy and Safety of Resistance Training for Coronary Heart Disease Rehabilitation: A Systematic Review of Randomized Controlled Trials - Fan, Yixuan; Yu, Meili; Li, Jingen; Zhang, He; Liu, Qiyu; Zhao, Lin; Wang, Tong; Xu, Hao (Frontiers in Cardiovascular Medicine, 2021)
Background: Resistance training (RT), as part of exercise prescriptions during cardiac rehabilitation for patients with cardiovascular disease (CVD), is often used as a supplement to aerobic training (AT). The effectiveness and safety of RT has not been sufficiently confirmed for coronary heart disease (CHD). Method: Three English and four Chinese electronic literature databases were searched comprehensively from establishment of each individual database to Dec, 2020. RCTs which compared RT with AT, no treatment, health education, physical therapy, conventional medical treatment (or called usually care, UC) in CHD were included. Methodological quality of RCTs extracted according to the risk of bias tool described in the Cochrane handbook. The primary outcomes were the index of cardiopulmonary exercise testing and the quality of life (QOL). The secondary outcomes included the skeletal muscle strength, aerobic capacity, left ventricular function and structure. Results: Thrity-right RCTs with a total of 2465 participants were included in the review. The pooling results suggest the RT+AT is more effective in the cardiopulmonary exercise function (peak oxygen uptake, peak VO2) , the physical score of QOL and global score of QOL, also in the skeletal muscle strength, the aerobic capacity and the left ventricular ejection fraction (LVEF) than AT group. However, there is insufficient evidence confirmed that RT+AT can improve the emotional score of QOL and decrease left ventricular end-diastolic dimension (LVEDD). No significant difference between RT and AT on increasing peak VO2 and emotional score of QOL. Moreover, the pooled data of results suggest that RT is more beneficial in increasing peak VO2, physical component and the emotional conditions of QOL and LVEF, and decreasing LVEDD than UC. Low quality evidence provided that RT had effect in decreasing rehospitalization events than UC. There is no significant difference in the safety of RT compared to AT. Conclusions: RT combined with AT is more beneficial than AT alone for CHD. RT can effectively improve the capacity of exercise and the QOL compared with UC. But the difference between RT and AT is still unknown. More high-quality and large-sample studies are needed to confirm our findings.